Program Kelas Unggulan Sebagai Strategi Kepala Madrasah Dalam Meningkatkan Prestasi Dan Positve Image - Muhammad Irfan Fauzi (JURNAL RISET MANAJEMEN (JURMA), 2024)
A superior class is a special space for students whose skills in a particular field are rated higher than other participants. Positive image is a type of belief in something or an impression that someone has because of their knowledge and understanding of a fact or reality. The focus of the research in this paper is: (1) how are superior classes used as a strategy for madrasah heads in improving achievement and positive image at Al-amiriyyah Madrasah Tsanawiyah (MTs) Blokagung Banyuwangi? (2) What are the supporting and inhibiting factors for the strategy of increasing achievement and positive image through superior classes at Madrasah Tsanawiyah (MTs) Al-amiriyyah Blokagung Banyuwangi? The method used by researchers here is a qualitative approach with a qualitative descriptive research type. The location of this research is Madrasah Tsanawiyah (MTs) Al-amiriyyah Blokagung, Tegalsari District, Banyuwangi Regency, East Java, from March 1 to 14. The research subjects were the head of the madrasah as the leader who manages everything in the madrasah and the students of Madrasah Tsanawiyah (MTs) al-Amiriyyah, and local residents or parents of the students of Madrasah Tsanawiyah (MTs) al-Amiriyyah. Data collection techniques are observation, interviews and documentation. Meanwhile, the data analysis is analysis of the interaction of 3 Milles and Hubberman models, namely data reduction, data presentation, drawing conclusions and also SWOT analysis is used to determine supporting and inhibiting factors.